CRITERIA USED BY PROFICIENT VS. LESS PROFICIENT EFL TEACHERS IN PRAGMATIC ASSESSMENT: THE CASE OF REQUEST SPEECH ACT - Misagh Hosseini; Ehsan Rezvani (University of Kuningan, 2018)
Abstract: The issue of EFL teachers’ rating criteria and patterns in Interlanguage pragmatics (ILP) assessment is new and needs rigorous analysis. The purpose of this study was to reveal important variables such as raters’ criteria and rating patterns by analyzing the ILP assessment process of Iranian non-native English speaking raters (NNESRs) of both high and low proficiency levels based on the request speech act. The data for this study was collected through a discourse completion test (DCT) and a rating questionnaire from 40 Iranian EFL teachers and were later analyzed through descriptive analysis-test and chi-squares. The results showed that raters considered 9 criteria, including pragma-linguistic and socio-pragmatic components of language which raters noted differently through eight request situations. The results showed that raters considered nine criteria, including pragma linguistic and socio-pragmatic components of language which were noted differently through eight request situations. Among the considered criteria, the highest frequencies belonged to the criteria of authenticity, query of preparatory and softness, and interlocutors’ relationship used by high proficiency teachers, whereas low proficiency teachers used the highest frequencies of accuracy, style, and directness. The result of the study can have important connotations for teachers to consider teaching L2 pragmatics in language classes and in teacher training courses.Keywords: Interlanguage pragmatics; request; speech act; pragmatic assessment.